The use of integrated activities in physical education classes - Pospelov, A.V. (Theory and Practice of Physical Culture, 2026)
The integration of the ‘Physical Culture’ course (the ‘Basketball’ module) with the subjects ‘Russian Language,’ ‘Mathematics,’ and ‘English’ in the elementary school curriculum promotes the development of meta-disciplinary universal learning activities among students. This approach ensures a more interconnected mastery of the curriculum. As a result, students become more aware of their learning activities, and the connection between theoretical knowledge and practical experience is strengthened.